Advertising in Malaysia - Mokhtar, Aida (Communication and Media Centre (COMET), IIUM, 2025)
This chapter is about advertising in Malaysia and the development of traditional and digital advertising. The nation has an ambiance that provides a special setting for its advertising mainly influenced by cultural, economic and political factors. Malaysia makes an interesting case study due to its rich history, unique population composition and Islam as the official religion allowing for the continuous mission for attaining an equilibrium between the diverse cultures.